(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
During the mobile technology’s global expansion, the widespread use of internet-enabled smartphones on all countries and especially in Asia Minor/Iraqi community has increased dramatically, as mobile applications became a key area of interest among physicians and patients in this society. Also, there are applications available that help healthcare providers, but these applications have limited possibilities and don’t have communication, monitoring, or other functions of healthcare. Physicians and patients turn to social media applications in the healthcare process. If we speak about Asia Minor, especially Iraq there are very few applications and related research that facilitates electronic health. Therefore, due to the conditions and requirements of the Iraqi health environment a healthcare solution called "MediCare" system that provides a medical social platform that facilitates interaction between hospitals, clinics, physicians, and patients has been developed. In this paper we present the implementation of the MediCare system together with its general architecture.